2016
DOI: 10.1007/s40090-016-0072-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of MEA and piperazine additives on the desulfurization ability of MDEA aqueous for natural gas purification

Abstract: The influence of monoethanolamine (MEA) and piperazine added into methyldiethanolamine (MDEA) aqueous solution on the desulfurization of natural gas was investigated by the method of equilibrium data determination in this paper. Four kinds of equilibrated systems, i.e. H 2 S-NG-MEA-water, H 2 S-NG-MDEA-water, H 2 S-NG-(MEA-MDEA)-water, H 2 S-NG-(MEA-MDEA-PZ)-water at the temperature ranging from 298.15 to 333.15 K were measured in a glass-jacketed gas absorption cell with a double-drive impeller device. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…For example, the molecule constructed by adding the methyl group to the α position of molecule A (hexane) was labeled as A-α-1. Three industrially applied compounds, 1-amino-3-hexanol (A-γ-10), piperazine (B-β-19), and p -xylylamine (C-γ-1), were selected to represent linear aliphatic amines, cyclic aliphatic amines, and aromatic amines, individually.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the molecule constructed by adding the methyl group to the α position of molecule A (hexane) was labeled as A-α-1. Three industrially applied compounds, 1-amino-3-hexanol (A-γ-10), piperazine (B-β-19), and p -xylylamine (C-γ-1), were selected to represent linear aliphatic amines, cyclic aliphatic amines, and aromatic amines, individually.…”
Section: Methodsmentioning
confidence: 99%
“…Nguyen et al 65 and Dash et al 66 reported that the blends of amines and PZ possess lower volatility than the amines alone as the blends typically form non-ideal solutions. On the other hand, Yunhai et al 15 evaluated the performance of MEA, MDEA, a mixture of MEA and MDEA and a mixture of MEA, MDEA and PZ for H 2 S capture from natural gas streams. They reported that the performance of MEA was the highest followed by the mixture of MEA, MDEA and PZ, the mixture of MEA and MDEA and MDEA, respectively.…”
Section: Technologies For H2s Capture and Removalmentioning
confidence: 99%
“…Yunhai et al [106] compared aqueous solutions of MEA, MDEA, MEA + MDEA, and MEA + MDEA + PZ for H 2 S absorption from pipeline natural gas that was supplemented with H 2 S during experiments. The ability of H 2 S absorption for the four systems is MEA > (MEA-MDEA-PZ) > (MEA-MDEA) > MDEA, demonstrating that addition of PZ increases the loading of H 2 S. However, this is not the case when both CO 2 and H 2 S are present in the feed gas.…”
Section: Alkanolaminesmentioning
confidence: 99%